2009
DOI: 10.1243/09544070jauto1187
|View full text |Cite
|
Sign up to set email alerts
|

Finite element analysis of the effect of up-armouring on the off-road braking and sharp-turn performance of a high-mobility multi-purpose wheeled vehicle

Abstract: A comprehensive finite element investigation is carried out of the effect of up-armouring on the off-road performance of a prototypical high-mobility multi-purpose wheeled vehicle. The effect of up-armouring on the vehicle performance was investigated under the following off-road manoeuvres: straight-line flat-land braking; straight-line off-angle downhill braking; sharp left turn. In each case, the appropriate vehicle performance criteria are identified and the parameters used to quantify these criteria are d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
29
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(29 citation statements)
references
References 17 publications
0
29
0
Order By: Relevance
“…Within this framework, the aforementioned equations are then solved using a second-order accurate explicit scheme. More details regarding the use of ABAQUS/Explicit in solving transient non-linear dynamics problems can be found in our previous work [23,24].…”
Section: Transient Non-linear Dynamics Analyses Of Fsp/coated-plate Imentioning
confidence: 99%
“…Within this framework, the aforementioned equations are then solved using a second-order accurate explicit scheme. More details regarding the use of ABAQUS/Explicit in solving transient non-linear dynamics problems can be found in our previous work [23,24].…”
Section: Transient Non-linear Dynamics Analyses Of Fsp/coated-plate Imentioning
confidence: 99%
“…Examples of finite element-based simulation of wheeled terramechanics applications can be found in Grujicic et al (2009), Hambleton andDrescher (2009), Mohsenimanesh et al (2009), Nankali et al (2012, Pruiksma et al (2011), Shoop et al (2006), Xia (2011), and Xia and Yang (2012). For an example of a full vehicle on soft soil refer to Grujicic et al (2009).…”
Section: Strength and Deformation Characteristicsmentioning
confidence: 99%
“…[11] studied the effect of change in materials by carrying out FEA analysis on connecting rod, reduction in the weight of connecting rod was observed by replacing the material from 4340 alloy steel to AlSiC-9 and found that AlSiC-9 is 61.65% lighter compared to 4340 alloy steel connecting rod. In last few decades, many researchers [12][13][14][15][16][17][18] have worked on optimization of automotive vehicle components to enhance the performance characteristics but major emphasis is given on engine components. In current study, the finite element analysis is carried out on the connecting rod to understand the design parameters like stress, strain, deformation etc.…”
Section: Introductionmentioning
confidence: 99%